2020
DOI: 10.3390/plants9010104
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Ascorbic Acid-Mediated Changes in Osmoprotection and Oxidative Defense System Enhanced Water Stress Tolerance in Different Cultivars of Safflower (Carthamus tinctorious L.)

Abstract: The present study was conducted to examine the effect of exogenously applied ascorbic acid (AsA) on osmoprotectants and the oxidative defense system in four cultivars (16171, 16183, 16207 and 16246) of safflower under well-watered and water deficit conditions. Water stress (60% field capacity) significantly decreased the shoot and root fresh and dry weights, shoot and root lengths and chlorophyll contents in all four safflower cultivars, while it increased the leaf free proline, total phenolics, total soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 37 publications
(54 reference statements)
6
55
0
Order By: Relevance
“…It also helps to transport electrons and acts as an antioxidant by neutralizing ROS, restoring the antioxidant form of vitamin E (Beyer, 1994;Prasad and Upadhyay, 2011;McGill and Jaeschke, 2013). Ascorbic acid (AsA) is believed to be one of the most efficient antioxidants against different stresses in plants especially in chickpeas (Zarghamnejad et al, 2014;Sharma et al, 2019;Farooq et al, 2020). Out of 33 released varieties used in this study, five varieties revealed high ascorbic acid, 23 were grouped into the intermediate category, and six varieties showed low AsA.…”
Section: Discussionmentioning
confidence: 98%
“…It also helps to transport electrons and acts as an antioxidant by neutralizing ROS, restoring the antioxidant form of vitamin E (Beyer, 1994;Prasad and Upadhyay, 2011;McGill and Jaeschke, 2013). Ascorbic acid (AsA) is believed to be one of the most efficient antioxidants against different stresses in plants especially in chickpeas (Zarghamnejad et al, 2014;Sharma et al, 2019;Farooq et al, 2020). Out of 33 released varieties used in this study, five varieties revealed high ascorbic acid, 23 were grouped into the intermediate category, and six varieties showed low AsA.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, exogenous application of vitamin C proved to be effective in protecting several plant species against drought stress. The assays were carried out in the grass “tall fescue” ( Festuca arundinacea Schreb, Xu et al, 2015 ), in wheat ( T. aestivum L., Hafez and Gharib, 2016 ) and safflower ( Carthamus tinctorius L., Farooq et al, 2020 ). The findings of Aziz et al (2018) are also interesting, since they tested the effects of pure synthetic ascorbic acid and natural sweet orange juice extract as a natural source of vitamin C, in quinoa ( Chenopodium quinoa ) under drought stress.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…Many stress-responsive genes have been analysed under different abiotic stress conditions (Chaturvedi et al, 2012;Chaturvedi et al, 2014;Jha et al, 2011;Jha et al, 2013;Udawat et al, 2014), which are extensively involved to various extent of stress tolerance and also in different stress-responsive regulatory pathways (Farooq et al, 2020;Singh et al, 2014a;Tiwari et al, 2014). Plants have evolved different mechanisms to respond to these stress conditions by employing gene products, which are broadly classified into two categories.…”
Section: Introductionmentioning
confidence: 99%
“…Stress endurance, from the perception of stress‐signals to the activation of a complex downstream signalling pathway, is a prerequisite for plants to acclimatise under adverse stress conditions which is regulated at molecular, cellular and physiological levels by the differential gene expression (Mishra & Tanna, 2017; Raja et al, 2020). Many stress‐responsive genes have been analysed under different abiotic stress conditions (Chaturvedi et al, 2012; Chaturvedi et al, 2014; Jha et al, 2011; Jha et al, 2013; Udawat et al, 2014), which are extensively involved to various extent of stress tolerance and also in different stress‐responsive regulatory pathways (Farooq et al, 2020; Singh et al, 2014a; Tiwari et al, 2014). Plants have evolved different mechanisms to respond to these stress conditions by employing gene products, which are broadly classified into two categories.…”
Section: Introductionmentioning
confidence: 99%